Influence of Hyperoxic-Supplemented High-Intensity Interval Training on Hemotological and Muscle Mitochondrial Adaptations in Trained Cyclists - Cardinale, D. A.; Larsen, F. J.; Lännerström, J.; Manselin, T.; Södergård, O.; Mijwel, S.; Lindholm, P.; Ekblom, B.; Boushel, R. (Frontiers in Physiology, 2019)
Background: Hyperoxia (HYPER) increases the O2 carrying capacity resulting in a higher O2 delivery to the working muscles during exercise. Several lines of evidence indicate that lactate metabolism, power output and endurance are improved by HYPER compared to normoxia (NORM). Since HYPER enables a higher exercise power output compared to NORM and considering the O2 delivery limitation at exercise intensities near to maximum, we hypothesized that hyperoxic-supplemented high-intensity interval training (HIIT) would upregulate muscle mitochondrial respiratory function and enhance endurance performance compared to training in normoxia. Methods: 23 trained cyclists, age 35.3±6.4 years, body mass 75.2±9.6 kg, height 179.8± 7.9 m, and VO2max 4.5±0.7 L·min-1 performed 6 wks polarized and periodized endurance training on a cycle ergometer consisting of supervised HIIT sessions 3 days/wk and additional low-intensity training 2 days/wk. Participants were randomly assigned to either HYPER (FIO2 0.30) or NORM (FIO2 0.21) breathing condition during HIIT. Mitochondrial respiration in permeabilized fibers and isolated mitochondria together with maximal and submaximal VO2, hematological parameters and endurance cycle performance were tested pre and post training intervention. Results: Hyperoxic training led to a small, non-significant change in performance compared to normoxic training (HYPER 6.0±3.7%, NORM 2.4±5.0%; p value = 0.073, ES= 0.32). This small, beneficial effect on performance was not explained by the change in VO2max (HYPER 1.1±3.8%, NORM 0.0±3.7%; p value = 0.55, ES= 0.08), blood volume and haemoglobin mass, mitochondrial oxidative phosphorylation capacity (permeabilized fibers: HYPER 27.3±46.0%, NORM 16.5±49.1%; p value = 0.37, ES= -3.24 and in isolated mitochondria: HYPER 26.1±80.1%, NORM 15.9±73.3%; p = 0.66, ES= -0.51), or markers of mitochondrial content which were similar between groups post intervention. Conclusions: This study showed that 6 wks hyperoxic-supplemented HIIT led to marginal gain in cycle performance in already trained cyclists but was not superior to conventional training at sea level in improving VO2max, blood volume, haemoglobin mass, nor mitochondrial oxidative phosphorylation capacity. Therefore, despite the small effect on cycling performance that might be meaningful in elite sport, considering the cost/benefit, health and ethical issues of performing hyperoxic-supplemented HIIT, this strategy to maximize endurance performance in already trained cyclists is controvertible.